Strategi Penanganan Burnout pada Siswa Anak Berkebutuhan Khusus di Sekolah: Tinjauan Literatur - Amalia Husen Titian, Farah; Suparwi, Sri (UNIVERSITAS SERAMBI MEKKAH, 2025)
Burnout in Children with Special Needs (CWSN) is a significant issue in educational settings, impacting their emotional, social, and academic well-being. This study aims to systematically review and evaluate strategies for managing burnout in CWSN by examining literature from reputable journals published over the past 10 years. Effective strategies identified include psychological interventions such as Cognitive Behavioral Therapy (CBT), relaxation techniques like mindfulness, and inclusive pedagogical approaches such as project-based learning and instructional differentiation. Social support from family, peers, and the community has also been found to play a crucial role in reducing the impact of burnout. The findings have practical implications for educators, counselors, and educational institutions in designing more effective and inclusive burnout management strategies. Future research should focus on developing more contextual and flexible approaches tailored to different social and cultural contexts.